2008
DOI: 10.1002/gps.2125
|View full text |Cite
|
Sign up to set email alerts
|

Persistent apathy in Alzheimer's disease as an independent factor of rapid functional decline: the REAL longitudinal cohort study

Abstract: In this study, a rapid loss in IADL score was partly explained by persistent apathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
64
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(69 citation statements)
references
References 22 publications
3
64
0
2
Order By: Relevance
“…Apathy is also significantly associated with depression in these individuals, although depression is neither necessary nor sufficient to produce apathy (Lechowski et al 2009). Alzheimer patients who develop apathy reportedly decline faster cognitively than those who do not manifest apathy (Lechowski et al 2009). In other dementias (including frontotemporal, Lewy body and vascular) as well as in mild cognitive impairment (MCI), the reported prevalence of apathy ranges from 38 to 95% (Robert et al 2006;Galvin et al 2007).…”
Section: Prevalence and Clinical Characteristicsmentioning
confidence: 97%
See 1 more Smart Citation
“…Apathy is also significantly associated with depression in these individuals, although depression is neither necessary nor sufficient to produce apathy (Lechowski et al 2009). Alzheimer patients who develop apathy reportedly decline faster cognitively than those who do not manifest apathy (Lechowski et al 2009). In other dementias (including frontotemporal, Lewy body and vascular) as well as in mild cognitive impairment (MCI), the reported prevalence of apathy ranges from 38 to 95% (Robert et al 2006;Galvin et al 2007).…”
Section: Prevalence and Clinical Characteristicsmentioning
confidence: 97%
“…It generally tends to afflict those with the greatest cognitive impairment and global disease severity (Starkstein et al 2006). Apathy is also significantly associated with depression in these individuals, although depression is neither necessary nor sufficient to produce apathy (Lechowski et al 2009). Alzheimer patients who develop apathy reportedly decline faster cognitively than those who do not manifest apathy (Lechowski et al 2009).…”
Section: Prevalence and Clinical Characteristicsmentioning
confidence: 98%
“…Among these variables, we think that the significant relationship that emerged between higher NPI scores at baseline and autonomy loss is particularly interesting. The role played by behavioral disturbances in the loss of autonomy in AD has yet to be completely clarified [41] ; recent data seem to show that a marked decline in autonomy is associated with a greater decrease in MMSE and a faster progression of behavioral disturbances, especially apathy [42,43] . The protective role of drugs other than AChEIs on mortality and disability that we found in our sample -mortality and autonomy loss were found to be lower in the subjects who took drugs -can be interpreted in the light of these considerations.…”
Section: Discussionmentioning
confidence: 99%
“…Apathy or executive dysfunctions, very frequent features in AD, can be assumed to contribute also strongly to functional decline, particularly persistent apathy [25][26][27][28] . In the present study, age was found to be a non-negligible factor for decline in BADL score.…”
Section: Discussionmentioning
confidence: 99%